Sufistic Values in the Story of the Meeting of the Prophet Moses and the Prophet Khidir in the Qur'an - Hamsah Awing; Rahmi Damis; Ahmad Mujahid; Nurchamidah; Fakih Hamdani; Muhammad Hamsah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the Sufi values ​​contained in the story of the meeting of the Prophet Moses and the Prophet Khidr as immortalized in the Qur'an, Surah Al-Kahf, verses 65-82. Through a Sufi hermeneutic approach, this study analyzes the esoteric dimensions of the story, including the concept of fana' fi al-syaikh, etiquette in pursuing the spiritual path, and the transformation of consciousness through surrender to the guidance of a spiritual teacher. The method used is textual analysis with an interpretative-qualitative approach to the text of the Qur'an and classical Sufi interpretations. The results of the study show that this story contains fundamental Sufi values ​​in the form of: (1) the concept of seeking laduni knowledge as knowledge obtained directly from Allah, (2) the importance of adab and tawadhu' in the student-teacher relationship, (3) the meaning of spiritual patience (sabr) in facing inner trials, and (4) the transformation from rational knowledge ('aql) to intuitive knowledge (kashf). These findings contribute to a deeper understanding of the Sufi dimension in the Qur'an and its relevance for the development of contemporary Islamic spirituality.